2014
DOI: 10.1097/ico.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Assisted Intracorneal Biopolymer Insertion for the Symptomatic Treatment of Bullous Keratopathy

Abstract: Intracorneal insertion of silicone oil is a feasible new technique for the symptomatic treatment of bullous keratopathy in blind eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Conjunctival flaps represent another option for these patients since they have very good results in alleviating ocular pain and discomfort but they may be related to several complications such as flap retraction [ 10 ]. Lastly, in blind eyes with BK, intracorneal silicone oil insertion has also been shown to result in immediate symptomatic relief [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival flaps represent another option for these patients since they have very good results in alleviating ocular pain and discomfort but they may be related to several complications such as flap retraction [ 10 ]. Lastly, in blind eyes with BK, intracorneal silicone oil insertion has also been shown to result in immediate symptomatic relief [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 111 ] Other case reports use FSL-assisted intrastromal pockets to implant intrastromal KeraKlear artificial cornea in congenital aniridia[ 112 ] or insert silicon oil as palliative management of bullous keratopathy in blind eyes. [ 113 ]…”
Section: Other Proceduresmentioning
confidence: 99%
“…These alternatives include hypertonic topical sodium chloride (5%) drops, bandage contact lenses, anterior stromal puncture, phototherapeutic keratectomy, amniotic membrane transplantation, conjunctival flaps, and collagen crosslinking (5-7). Recently, Kymionis et al (9) reported that a new technique had alleviated the pain of bullous keratopathy in eyes with no visual potential. The authors described a corneal pocket formed with a femtosecond laser and silicone oil added to this pocket to prevent overhydration of the cornea and the development of epithelial edema.…”
Section: Introductionmentioning
confidence: 99%